Comparison of the amorphization ability of two polymorphic forms of Olanzapine - Chendo, Catarina (2019)
Poster presented at the 4th International Congress of CiiEM - "Health, Well-being and Ageing in the XXI Century." 2-5 June 2019, Campus Egas Moniz, Monte de Caparica, Portugal